Youth religiosity as a mediator of the relationship between psychosocial factors and positive youth development - Mohamed, Nor Hidayah; Hamzah, Siti Raba’ah; Ismail, Ismi Arif; Abu Samah, Bahaman (Whioce Publishing, 2018)
The objective of this study was to investigate the mediating role played by youth religiosity in the relationship between the psychosocial factors of parental attachment, peer attachment, and institutional social bonding with positive youth development (PYD). PYD was based on the 5Cs (competence, confidence, connection, character, caring & compassion)model. This study involved a cluster sampling of 677 youths in Malaysian community colleges; their ages ranged from 18 to 23 years (M = 19.47; SD = 3.59). Data were collected via self-administered questionnaires. The findings indicated that youth religiosity fully mediated the relationships of parental attachment, as well as peer attachment with PYD. Religiosity also partially mediated the relationship between institutional social bonding and PYD. Hence the findings suggest that youth religiosity, which comprises ritualistic and prosocial behaviour, contributed considerably to positive.